2012
DOI: 10.1038/aps.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism-based pharmacokinetic/pharmacodynamic model for CYP3A1/2 induction by dexamethasone in rats

Abstract: Aim: To develop a pharmacokinetic/pharmacodynamic (PK/PD) model describing the receptor/gene-mediated induction of CYP3A1/2 by dexamethasone (DEX) in rats. Methods: A group of male Sprague-Dawley rats receiving DEX (100 mg/kg, ip) were sacrificed at various time points up to 60 h posttreatment. Their blood sample and liver were collected. The plasma concentration of DEX was determined with a reverse phase HPLC method. CYP3A1/2 mRNA, protein levels and enzyme activity were measured using RT-PCR, ELISA and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…In rat, CYP3A2 is the main constitutive liver enzyme; sharing 73% homology in the amino acid sequence, some substrate preference and functional analogies to human CYP3A4 [71], which metabolizes a wide range of drugs and endogenous compounds. Our finding that MPL enhances CYP3A2 expression in the rat is in line with previous findings that dexamethasone (DEX) induces CYP3A2 mRNA and protein expression as well as enzyme activity in rat liver [72]. …”
Section: Resultssupporting
confidence: 92%
“…In rat, CYP3A2 is the main constitutive liver enzyme; sharing 73% homology in the amino acid sequence, some substrate preference and functional analogies to human CYP3A4 [71], which metabolizes a wide range of drugs and endogenous compounds. Our finding that MPL enhances CYP3A2 expression in the rat is in line with previous findings that dexamethasone (DEX) induces CYP3A2 mRNA and protein expression as well as enzyme activity in rat liver [72]. …”
Section: Resultssupporting
confidence: 92%
“…However, a previous study showed that PXT inhibited the expression of CYP3A1/2 mRNA in rat primary hepatocytes. CYP3A1/2 was predominant in rat liver, whereas CYP3A4 was predominant in human hepatocytes and HepG2 cells (Li et al, ). The species difference in CYP3A enzymes and their nuclear receptors between humans and rats may be a crucial factor explaining this differential regulation effect.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC ratio (MDZ) is the increase in MDZ exposure due to ABT when compared with the MDZ exposure without ABT pretreatment. The rate constant for enzyme degradation in the liver, k deg,h , was fixed to the literature value of 6.9 × 10 −4 min −1 . The average concentration of ABT over 24 h from each study was used as [ I ] h .…”
Section: Methodsmentioning
confidence: 99%
“…The rate constant for enzyme degradation in the liver, k deg,h , was fixed to the literature value of 6.9 × 10 À4 min À1 [15]. The average concentration of ABT over 24 h from each study was used as [I] h .…”
Section: In Vitro Studiesmentioning
confidence: 99%